Tunable mid-infrared and far-infrared surface plasmons in doped semiconductor and semimetal structures - Tao, Jin (2015)
Surface plasmons (SPs) are the electromagnetic (EM) waves due to the light coupled with surface charge oscillations at the interface between metal and dielectric. SPs are widely investigated in the visible and near-infrared wavelengths range due to their capabilities to enhance, guide, and manipulate EM wave on the subwavelength scale. At these wavelengths they have been served as enabling mechanisms from fundamental science to many applications, such as nonlinear harmonic generation, cavity quantum electrodynamics, high-performance sensor, ultracompact interconnects, high resolution microscopy and photolithography. Successful adoption of SP-inspired solutions in the mid-infrared (IR) and far-IR regions will give benefits to fields of environment and health, security and defense, communication and detection such as chemical sensing, thermal imaging, beam shaping and steering, and high-performance detectors. However, the existing knowledge of SPs in visible/near-IR wavelengths cannot directly used in mid- and far-IR regimes as the optical responses to the metal in these two wavelength regions are quite different. In the mid-IR wavelength and beyond, the conventional noble metals resemble perfect electrical conductors, and SPs mode weakly penetrates into metal and the interaction between electrons in metal and the oscillating EM wave is instantaneous. As a result, most the EM field penetrates to the dielectric side and SP mode is weekly confined, which limits many important applications needing strong field confinements. In this thesis, we proposed several approaches to guide and manipulate surface plasmons in mid- and far-IR region with strong field confinement. We mainly used doped semiconductors of indium antimonide (InSb) and graphene for these wavelengths regimes. In the chapter 2, we proposed tunable subwavelength terahertz plasmonic stub waveguide filters based on InSb whose permittivity is similar to that of metals at optical frequencies, thus it provides good field confinement. In addition, the permittivity of InSb can be modified by varying temperature, dopant concentrations and magnetic fields which can be used to realize the tunability of plasmonic devices. We used the transmission line theory and the Finite Different Time Domain to investigate the optical responses of the single-stub and multiple-stub waveguide structures. The results show that the proposed structure can realize tunable narrow-and wide-stop band filtering functions. In the following sections of this thesis, we mainly discussed graphene surface plasmons. The two dimensional semimetal — doped graphene, has also been found as a promising platform for plasmonic applications in the IR frequency regime owing to an unprecedented spatial confinement and tunability by electrostatic gating. In addition, graphene exhibits a relatively large conductivity which translates into long optical relaxation times, and thus could potentially provide a large plasmon wave propagation distance. Efficient excitation of plasmons on graphene still remains a challenge owing to the large wave-vector mismatch between the optical beam in air and graphene plasmon. Current approaches to excite graphene plasmons mainly depend on the grating coupling method, which requires a nanoscale patterning of either graphene itself or the underlying substrate, but the scattering of plasmons from these patterned edges will significantly reduce the plasmon lifetime. In chapter 3, we presented a novel scheme capable of exciting graphene plasmons on a flat suspended graphene by using only s-polarized optical beams through four-wave mixing (FWM) process, where the graphene surface plasmons fields were derived analytically based on the Green's function method, under the basis of momentum conservation. Much attention has been focused on localized graphene surface plasmons resonance with the incident light from free space, such as nano-ribbons, nano-disks, graphene-metal plasmonic antennas and graphene metamaterials. It is also interesting and indispensable to study the propagation properties of graphene plasmon waves. In the chapter 4, we proposed and numerically analyzed a plasmonic Bragg reflector formed in graphene waveguide. The results show that the graphene plasmonic Bragg reflector can produce a broadband stopband, which can be tuned over a wide wavelength range by a small change in Fermi energy level of graphene. By introducing a defect into the Bragg reflector, we can achieve a Fabry-Perot-like microcavity with a quality factor of 50 for the defect resonance mode formed in the stopband. Plasmon losses remain the main obstacle for implementation of such devices. In the chapter 5, we performed near-field microscopic experiments at the wavelength of 10 μm and showed that a substantial reduction of plasmon damping can be achieved by placing a nanometric polymer nano-dots spacer between the graphene layer and the supporting silicon oxide slab making graphene quasi-suspended. We argued that reduction of plasmon losses is attributed to weaker coupling with substrate phonons in the quasi-suspended graphene.